Sensitivity of the Point-of-Care Circulating Cathodic Antigen Urine Cassette Test for Diagnosis of Schistosoma mansoni in Low-Endemicity Settings in Côte d’Ivoire - Assaré, Rufin K. (Am J Trop Med Hyg, 2018)
The sensitivity of a point-of-care circulating cathodic antigen (POC-CCA) urine cassette test for diagnosis of Schistosoma mansoni in low-endemicity settings is poorly understood. We conducted a cross-sectional survey in 14 villages in western Côte d’Ivoire and diagnosed children aged 9–12 years for schistosomiasis. Two stool samples were subjected to triplicate Kato–Katz thick smears each for diagnosis of S. mansoni, whereas a single urine sample was examined by POC-CCA for S. mansoni, filtration for Schistosoma haematobium, and reagent strip for microhematuria. According to the Kato–Katz technique, we found 45 out of 681 children positive for S. mansoni (6.6%) with a mean intensity among infected children of 72.2 eggs per gram of stool. Point-of-care circulating cathodic antigen revealed a prevalence of S. mansoni of 33.0% when trace results were considered positive and 12.5% when trace results were considered negative. Eggs of S. haematobium were found in eight participants (1.2%), whereas the prevalence of microhematuria was 13.5%. A single POC-CCA urine cassette test revealed a several-fold higher prevalence of S. mansoni than multiple Kato–Katz thick smears in this low-endemicity area. Our findings have important ramifications for choosing an appropriate diagnostic tool in low-endemic areas that might be targeted for elimination.